The Diaries of the Maryknoll Sisters in Hong Kong, 1921–1966
XI, 241 p. 2 illus.
Keywords: This book is a documentary survey of Hong Kong history, from the 1920s to the mid-1960s, from the perspective of the Maryknoll Sisters, as recorded in their diaries written during that period. It is a priceless collection of first-hand materials on the social history of Hong Kong.